Groundwater in the northwestern coastal region of Libya.: Groundwater in the northwestern coastal region of Libya. (jornal of the libyan geographical society, 2009)
Groundwater in the western coastal region is found at varying depths. Its quality, productivity, and suitability for providing sufficient quantities for various human needs, agricultural requirements, and other consumption purposes all differ.In addition to the locations of its presence according to the type of rocks, most of the water-bearing layers date back to the Quaternary and Tertiary periods, which necessitates a detailed discussion of the presence of groundwater in each layer, according to the geological period to which it dates back.
Keywords: Groundwater; Coastal area; Agriculture; Fourth time; The third time; Geological time